2015
DOI: 10.1073/pnas.1502588112
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell division patterns in the Arabidopsis shoot apical meristem

Abstract: The stereotypic pattern of cell shapes in the Arabidopsis shoot apical meristem (SAM) suggests that strict rules govern the placement of new walls during cell division. When a cell in the SAM divides, a new wall is built that connects existing walls and divides the cytoplasm of the daughter cells. Because features that are determined by the placement of new walls such as cell size, shape, and number of neighbors are highly regular, rules must exist for maintaining such order. Here we present a quantitative mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
54
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 24 publications
6
54
2
Order By: Relevance
“…Consistent with previous studies3835, we found that ∼60% of divisions produced daughters with >5 μm 2 difference in outer cell surface area at birth, equivalent to inheriting on average >54% of the parental area (Supplementary Fig. 2a,b).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies3835, we found that ∼60% of divisions produced daughters with >5 μm 2 difference in outer cell surface area at birth, equivalent to inheriting on average >54% of the parental area (Supplementary Fig. 2a,b).…”
Section: Resultssupporting
confidence: 92%
“…Analysis of cell growth rates in the SAM suggests cell size control is required35 and indeed most models of plant tissue growth assume that cell division is triggered when cells reach a defined cell size36373839. However no cell-sizing mechanism has been proposed or identified for plant cells, and little is known about how cells behave when variation in cell size arises, or how changes in cell size are regulated during development.…”
mentioning
confidence: 99%
“…The mean interdivision time was 21-31 h among SAMs, which is similar to a previous time-lapse imaging study of SAMs not grown on NPA (15). Our data confirmed reported distributions of L1 cell neighbor numbers, outer periclinal wall areas, and the linear relation (Lewis' law) between number of neighbors and outer periclinal wall area (32)(33)(34)(35) (Fig. 1E and SI Appendix, Figs.…”
Section: Resultssupporting
confidence: 91%
“…These geometric rules were also tested in the Arabidopsis shoot apical meristem (SAM), a dome-shaped group of dividing cells that generates every aerial organ. Although Errera's rule described the highest percentage of divisions, neither Hofmeister's, nor Errera's, nor Sachs' rules fully described all of the divisions at the SAM (7).…”
mentioning
confidence: 87%